Peran Ilmu Kemanusiaan Dalam Meningkatkan Mutu Manusia Indonesia Melalui Perlindungan Anak Dalam Rangka Mewujudkan Anak Indonesia yang Sehat, Cerdas Ceria, Berakhlak Mulia dan Terlindungi - Tb. Rachmat Sentika (Fakultas Seni Rupa dan Desain ITB, 2007)
Enhancement of humans' life-quality must become a focus & major issue on analy-zing HSc (humanity science).Because HSc plays a decisive role in tridarma(3duties) of higher-learning institution which may aim to the utmost purpose for national interests. Main chapter of humans' life-quality, is children protection.For they consist 40% of total Indonesian population, especially Indonesia had ratified CONVENTIONS on Child-ren-rights.However, we have not publicized it, such an incompetence greatly hampers the accomplishment of children protection. Supposedly, government real-efforts are in creating children protection environs, imp-roving values & traditions.Which in turns, to forward children's respect &.dignity. Along to explore the mobilization of their resource to back up children protection accomplishment.